A short peptide for efficient cellular mRNA delivery: A potential application for inducing an immune response - Clémentine Ayélé Teko-Agbo; Emilie Josse; Karidia Konate; Sébastien Deshayes; Pascal de Santa Barbara; Sandrine Faure; Prisca Boisguérin; Eric Vivès (Molecular Therapy: Nucleic Acids)
Nucleic acid molecules are emerging as potential therapeutic tools, as evidenced by the transfection of small interfering RNA (siRNA) molecules in therapeutic applications and messenger RNAs in immunotherapeutic vaccination. In most cases, these nucleic acids are conditioned as lipid nanoparticles made with different lipid moieties to promote their intracellular delivery. Over the past few years, we have documented the delivery of siRNAs using a single short (15 amino acids) peptide called WRAP5, which follows an extremely simplified formulation phase that enables the formation of nanoparticles with a diameter of 60–80 nm. We indeed demonstrated the expected dose-response reduction in the levels of the targeted proteins. To apply this technology to the cellular delivery of mRNAs, we investigated the ability of the WRAP5 peptide to transfect mRNAs of different sizes and promote the expression of their proteins. These peptide-based nanoparticles, which also have diameters ranging from 60 to 80 nm, showed remarkable stability over time when simply stored at 4°C and fully retained their transfection properties in vitro for up to several months post-formulation. Interestingly, we demonstrated in vivo that these nanoparticles were able to induce an immune response against the protein synthesized from the vectorized mRNA.